Pythium insidiosum keratitis in contact lens wear: a case report. - Kaevalin Lekhanont (2018)
PURPOSE: The purpose of this study was to report a case of contact lens-related Pythium insidiosum corneal ulcer. METHODS: The authors conducted an interventional case report. We report the clinical presentations, histopathologic findings, and treatments of a patient with P. insidiosum keratitis associated with contact lens wear. RESULTS: A 22-year-old Thai woman presented to our clinic with a nonresponsive, progressive corneal ulcer of the left eye. Slit lamp examination showed a large central ulcer measuring 5.4 x 5.2 mm with underlying dense stromal infiltrates surrounded by subepithelial and superficial stromal opacity in a reticular pattern along with radial perineural-like infiltrates. Histopathologic examination revealed broad, branched, thin-walled nonparallel hyaline hyphae with rare septates consistent with P. insidiosum. The corneal culture confirmed the diagnosis. The infection recurred after multiple therapeutic penetrating keratoplasties. Enucleation was eventually performed to eradicate the infection. No definite report of contact lens-related P. insidiosum keratitis existed in the literature. CONCLUSION: Pythium keratitis may present with central ulcer and radial keratoneuritis similar to acanthamoeba keratitis. Contact lens wear can be a risk factor for this infection. Increasing awareness, early diagnosis, and intervention may improve the prognosis.